Enhancing the Budget Impact Model for Institutional Use: A Tool with Practical Applications for the Hospital Oncology Pharmacy. Issue 6 (June 2016) - Hess, Lisa M.; Cinfio, Frank N.; Wetmore, Stewart; Churchill, Collin; Fausel, Christopher; Ale-Ali, Amine; Gelwicks, Steven; Bly, Christopher A.; Perk, Sinem; Klein, Robert W.
Background: The cost of cancer care is increasing, and tools are needed to understand the economic impact of new drugs on the hospital pharmacy budget. Objective: To develop an interactive budget impact model (BIM) through a collaborative effort of industry, academia, and modeling experts to evaluate the use of a new agent in non-small cell lung cancer (NSCLC); this BIM included an institutional module specific to the needs of practices that purchase medications for use in institutional settings. Methods: Treatment regimens, doses, duration of therapy, toxicity, and cost data are from published sources. All input data may be modified to match the local population. Outputs include cost of care, reimbursement, and margin overall and by treatment regimen. Results: The base case assumes 20 NSCLC patients progressing after initial therapy (3 receiving ramucirumab+docetaxel, 2 bevacizumab+erlotinib, 3 docetaxel, 6 erlotinib, and 6 pemetrexed), wholesale acquisition cost (WAC) purchase price, and reimbursement at WAC+4.3%. The model estimated the total cost and reimbursement for the institutional oncology pharmacy to be $699, 413 and $729, 487, respectively, resulting in a margin of $30, 075 (difference due to rounding) for the year for regimens utilized in the treatment of NSCLC in the post-progression setting. Results will vary depending on the input data. Conclusions: There is an increasing need for institutional pharmacies to plan ahead and anticipate the impact of new drugs on their oncology budgets. This interactive Excel-based institutional BIM may provide evidence-based support for pharmacy decision making.